The State of Palliative Care Education in United States Physical Medicine and Rehabilitation Residency Programs: Heterogeneity and Opportunity for Growth. (16th December 2022) - Tolchin, Dorothy Weiss; Brooks, Forrest A.; Knowlton, Tiffany
Abstract: Physical medicine and rehabilitation physicians routinely care for patients with serious illness and injury who could benefit from an integrated palliative care approach due to the propensity for high or complex symptom burden. Despite this, it has been unknown whether and how physical medicine and rehabilitation residency programs are equipping residents with a foundational palliative care skillset. We report national survey results characterizing the current status of palliative care education within US physical medicine and rehabilitation residency programs. Programs vary widely in the type and amount of palliative care education provided, with nearly a third of responding programs reporting no palliative care education at all. These findings suggest the need for nationally unifying palliative care education standards for physical medicine and rehabilitation residency programs to ensure that all physical medicine and rehabilitation residents have the opportunity to develop a robust palliative lens that can be applied across rehabilitation practice settings. An articulated set of standards could both facilitate achievement of palliative care–specific objectives and support achievement of foundational physical medicine and rehabilitation residency program objectives.